PD-L1 Expression Is Associated With VEGFA and LADC Patients' Survival - Liu, Shaochuan; Qin, Tingting; Jia, Yanan; Li, Kai (Frontiers in Oncology, 2019)
Objectives: To elucidate the relationship between VEGFA and PD-L1 expression in lung adenocarcinoma (LADC). Methods: PD-L1 and VEGFA expression were determined by immunohistochemistry with H-score on formalin-fixed paraffin-embedded resected LADC specimens of 129 cases. Results: High PD-L1 expression in 53 (41.1%) patients, high VEGFA expression in 65 (50.4%) and co-expression in 18 (14.0%) were observed. Inverse correlation between expression of PD-L1 and VEGFA was found (P = 0.002, r = -0.274). VEGFA and PD-L1 expression were not significantly associated with the clinicopathological features. High PD-L1 expression was significantly association with all patients’ poor progression-free survival and overall survival in an univariate analysis, but there was no significantly association with high VEGFA expression and prognosis. Co-expression of PD-L1 and VEGFA exhibited a worst overall survival compared to negative groups (P = 0.005). Conclusions: These findings indicate that high PD-L1 expression could forecast both poor overall survival and progression-free survival in patients with resected LADC. Co-expression of PD-L1 and VEGFA may be considered as an important predictor for prognosis of patients with resected lung adenocarcinoma.